2020
DOI: 10.4103/ijri.ijri_308_19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a standardized reporting format on the quality of MRI reports for rectal cancer staging

Abstract: Background and Aims: Besides providing a surgical roadmap, rectal MRI plays a major role in treatment planning. We recently started using a structured template for reporting rectal cancer via MRI. We study the impact of using this template at our hospital in terms of number of essential imaging parameters described in the reports as compared to the pre-template free-text reports. Methods: A structured rectal MRI reporting template was created in consensus with members of the colorectal tumour board and was int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Overview of articles with level A and B evidence which studied structured reporting in radiology. Presented is the level of evidence, control group, intervention, subspecialty/field, indication, modality and outcome(s) Level of evidence Control Intervention Subspecialty/field Indication Modality Outcome(s) Structured layout (SR level 1) — one template Dimarco et al (2020) [ 14 ] B Free text Structured itemized template with four parts and several key items Abdomen Pancreatic ductal adenocarcinoma CT Significant reduction of missing morphological and vascular features Improvement inter-reader agreement Gupta et al (2020) [ 15 ] B Free text Added 14 essential parameters Abdomen Rectal cancer staging MRI Significant report quality improvement Referring provider satisfaction improved McFarland (2020) [ 16 ] B Free text Free-form structured itemized templates Abdomen Various CT Less reporting errors potentially reducing The report word length did not differ Olthof et al (2020)[ 17 ] B Free text Additional template with key items for critical findings Neurology CNS metastasis MRI Automated insertion of context-dependent data and required elements is feasible Guideline adherence concerning critical findings improved Alessandrino et al (2019)[ 18 ] B Free te...…”
Section: Resultsmentioning
confidence: 99%
“…Overview of articles with level A and B evidence which studied structured reporting in radiology. Presented is the level of evidence, control group, intervention, subspecialty/field, indication, modality and outcome(s) Level of evidence Control Intervention Subspecialty/field Indication Modality Outcome(s) Structured layout (SR level 1) — one template Dimarco et al (2020) [ 14 ] B Free text Structured itemized template with four parts and several key items Abdomen Pancreatic ductal adenocarcinoma CT Significant reduction of missing morphological and vascular features Improvement inter-reader agreement Gupta et al (2020) [ 15 ] B Free text Added 14 essential parameters Abdomen Rectal cancer staging MRI Significant report quality improvement Referring provider satisfaction improved McFarland (2020) [ 16 ] B Free text Free-form structured itemized templates Abdomen Various CT Less reporting errors potentially reducing The report word length did not differ Olthof et al (2020)[ 17 ] B Free text Additional template with key items for critical findings Neurology CNS metastasis MRI Automated insertion of context-dependent data and required elements is feasible Guideline adherence concerning critical findings improved Alessandrino et al (2019)[ 18 ] B Free te...…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al conducted a study to determine how using a specific template for reporting rectal cancer via MRI impacted a hospital [ 7 ]. The researchers created a template that contained 14 necessary parameters to be included in the reports.…”
Section: Discussionmentioning
confidence: 99%
“…The survey showed that 100% of respondents felt less need to speak with the radiologist to clarify the report, 81.8% felt an improvement in the report's quality compared to free-style reports, and 91% felt that the new template was easier to interpret. The template increased the number of necessary imaging parameters mentioned in the reports, reducing the need for clarification, and improving the overall quality of reporting [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation